Advancement of Noise, Vibration and Harshness (NVH) Performance of Vehicle Rubber Hoses - Jung, H.S.; Lee, S.H.; Woo, H.S.; Kim, M.S.; Park, H.H.; Min, B.K. (Asian Journal of Chemistry, 2013)
This study assessed an approach in terms of materials for improving the noise, vibration and harshness (NVH) performance of a rubber hose. Ethylene propylene rubber for the heater hoses in a cooling system and acrylic rubber (AR) for the intercooler hose in an air intake system were chosen for mixing to improve the vibration and noise performance. Both ethylene propylene rubber and acrylic rubber were modified by changing the compound of the base polymer, reinforcement filler and additives. Dynamic mechanical analysis was used to measure the viscoelastic properties, such as the storage modulus and loss factor (tan d). A vehicle acceleration test was also conducted to observe the indoor changes in the NVH performance of rubber hoses.